Investigation On The Etiology Of Subclinical Mastitis In Jersey And Hybrid Jersey Dairy Cows - Hande Gürler (Sciendo, 2015)
The aim of this study was to investigate the etiology of subclinical mastitis (SCM) in dairy Jersey cows with the use of bacteriological and molecular identification methods. In the study 121 Jersey and 78 hybrid Jersey cows with SCM were observed in the Samsun district of Turkey. A total of 411 California mastitis test (CMT) positive milk samples from these animals were examined bacteriologically. The prevalence of subclinical mastitis was 54.75% and 67.2% in Jerseys and hybrids, respectively. On bacteriological examination, a total of 92 strains were isolated from 411 milk samples. The most prevalent bacteria were Staphylococcus spp. (69.56%). Among them 24 isolates were Staphylococcus aureus (26.08%) the other isolates were Streptococcus dysgalactiae (23.91%), Enterococcus spp. (3.26%) and Streptococcus agalactiae (3.26%). All strains were identified with bacteriological culture methods, as well as by Polymerase Chain Reaction (PCR). Gram-negative bacteria were not isolated. In conclusion, the etiology of SCM in full blood and hybrid Jersey dairy cows in Samsun and the prevalence of bacteria were determined. The relatively high prevalence of SCM indicates the potential need for the consideration of some factors contributing to the formation of mastitis (e.g. management) as well as bacterial agents. The present study and further studies may be useful to develop mastitis vaccines by means of providing true vaccine strain sources.